2020
DOI: 10.1021/acs.iecr.9b05426
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Availability and the Nature of Extracellular Organic Matter of Microalgae

Abstract: Microalgae have the ability to assimilate atmospheric carbon dioxide and organic and inorganic pollutants while simultaneously producing a range of useful intracellular metabolites. Harvesting and concentrating microalgal suspensions, which is commonly performed via coagulation, flocculation, or filtration, is complex, owing to the dynamic character of the cells. The availability of nitrogen to the cells plays a crucial role in the synthesis of intracellular products and in the release of extracellular organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…They simultaneously assimilate CO 2 and organic and inorganic pollutants and produce a range of useful intracellular metabolites. Baroni et al investigated the role of nitrogen availability in the production and release of extracellular matter in three commercially relevant microalgae . Variations of extracellular substances, in relation to microalgae species and cultivation conditions, were reported, with important implications for species selection and optimization of microalgae production, harvesting, and dewatering processes.…”
Section: Co2 Utilization and The Chemical Industrymentioning
confidence: 99%
“…They simultaneously assimilate CO 2 and organic and inorganic pollutants and produce a range of useful intracellular metabolites. Baroni et al investigated the role of nitrogen availability in the production and release of extracellular matter in three commercially relevant microalgae . Variations of extracellular substances, in relation to microalgae species and cultivation conditions, were reported, with important implications for species selection and optimization of microalgae production, harvesting, and dewatering processes.…”
Section: Co2 Utilization and The Chemical Industrymentioning
confidence: 99%
“…The nature of EOM varies with the growth stage and is also affected by nitrogen availability in the media. Under nitrogen-replete conditions, most EOM is composed of protein, while under nitrogen-deplete conditions, adopted for lipid induction, EOM is mainly composed of polysaccharides ( Baroni et al, 2020 ). Growth was severely inhibited during the third cycle, and bacteria were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that a decrease in nitrogen is directly proportional to the decrease in total proteins produced. Recently, Baroni et al. (2020) examined extracellular organic matter (EOM), specifically the protein and carbohydrates, in several microalgae with a ratio of nitrogen supply in kultur.…”
Section: Resultsmentioning
confidence: 99%